Symbol Digit Modalities Test: A valid clinical trial endpoint for measuring cognition in multiple sclerosis. (November 2019) - Strober, Lauren; DeLuca, John; Benedict, Ralph HB; Jacobs, Adam; Cohen, Jeffrey A; Chiaravalloti, Nancy; Hudson, Lynn D; Rudick, Richard A; LaRocca, Nicholas G; ,
Background: The need for more robust outcomes in multiple sclerosis (MS) clinical trials has been a main priority of the field for decades. Dissatisfaction with existing measures has led to several consensus meetings and initiatives over the past few decades in hopes of defining and gaining acceptance of measures that are valid, reliable, sensitive to change and progression, and most importantly, relevant to those living with MS. The Multiple Sclerosis Outcome Assessments Consortium (MSOAC) was formed for this purpose. Objective: The objective of this paper is to describe the results of the MSOAC plan to obtain qualification for a cognitive performance measure that meets these requirements. Methods: Using data from 14 MS disease-modifying registration trials, we completed a comprehensive examination of the psychometric qualities of the Symbol Digit Modalities Test (SDMT) and the Paced Auditory Serial Addition Test (PASAT) with the goal of compiling evidence to support the utilization of one of these measures in future clinical trials. Results and conclusion: Consistent with the published literature, the SDMT proved superior to the PASAT. The SDMT should be considered the measure of choice for MS trials in assessing cognitive processing speed.